World Agriculture Before and After 1492 Legacy of the Columbian Exchange - Hancock, James F. (Cham : Springer International Publishing : Imprint: Springer, 2022)
The year 2022 is the 50th anniversary of Alfred Crosby's celebrated book - The Columbian Exchange: Biological and Cultural Consequences of 1492. In the book, Crosby was the first to discuss the impact that the Spanish and Portuguese colonial period had on world agriculture and human culture. How the crops of the world became homogenized, and how an indigenous culture was destroyed by disease after Columbus landed. His landmark study broke new ground in its broad conceptualization of the Atlantic exchange. Building on what Crosby so succinctly and brilliantly presented, the main goal of this new work is to present the depth of information that has emerged since "The Columbian Exchange" and to discuss more fully the development of crops and agriculture before and after the Iberian contact. It follows the journey of crops and livestock in the Old and New Worlds and end's with their distribution in today's world.
Introduction -- Origins Of World Crops And Livestock -- Evolution Of European Agriculture -- Agriculture In The Americas Before The European Conquest -- Spanish Conquest And Colonization Of The Americas -- Advance Of Spanish Agriculture In Colonial America -- Portugal And The South Atlantic Exchange -- The Two Worlds Become One -- Dispersal Of New World Crops Into The Old World -- Five Hundred Years After The Great Encounter -- Index.
Keywords: Agriculture; Plant ecology; Plants-Evolution.; Science-History.; Agriculture; Plant Ecology; Plant Evolution; History of Science